The Use of Three Techniques to Control the Pest of “Walang Sangit” (Leptocorisa oratorius F.) on White Glutinous Rice (Oryza sativa L. var glutinosa) - Siregar, Ameilia Zuliyanti; Ikhwan, Muhammad Awwalul (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2024)
“Walang sangit” (Leptocorisa oratorius) is important pest of paddy rice plantation during generative phase. The objective of this experiment was to determine the use of three techniques to control the pests L.oratorius on white sticky rice plants at Harmonika Baru, Padang Bulan Selayang II, Medan Selayang District, Medan. The insects collected were identified at the Pest Laboratory, Faculty of Agriculture, University of Sumatra Utara from May to October 2023. This experiment used purposive sampling method with 3 types of treatments, including: application of golden snail carcass traps, papaya leaf extract, and used of Beauveria bassiana. The results showed that the insects caught in the three treatments had the same number of orders and families (5 Orders and 19 families) with 2593 individuals with application of golden snail carcass trap,743 individuals by application of papaya leaf extract, and 528 individuals by spraying of Beauveria bassiana. The score calculation of AD1 were 2.593 individual while AF1 were 359; AD2 were 743, AF2 were 138; AD3 were 528 individuals, AF3 were 137 individuals. The Richness index (R) was 7.57 (R1), 7.67 (R2), and 2.64 (R3). The evenness index (E) was E1 = 0.80, E2 = 0.80, and E3 = 0.75. The dominance index (C) was 1 for three treatments, while insect diversity index (H’):H’1=2.48; H’2=2.64; H’3=2.70.We concluded that the application of golden snail carcass traps was the best treatment. Three types of insect function status were identified are herbivores, predators and scavengers. Keywords: Beauveria bassiana, carcass trap, papaya leaf, white sticky rice